Informatization and Paradigm Change in Islamic Higher Education - Maisah, Maisah; Nasution, Faisal Hakim; MY, Mahmud; Junaidi, Roni (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2025)
Islamic higher education currently faces significant challenges due to the transformation of information technology and digitalization, which have the potential to erode Islamic identity. The goal of this study is to examine the integration of informatization into Islamic higher education and pinpoint the necessary paradigm shifts for cultivating graduates with robust character and professional skills. The study employs a qualitative approach, incorporating phenomenology and documentation techniques, to comprehensively collect and analyze data. The results of the study indicate that the application of technology in the curriculum, teaching methods, and academic administration can improve efficiency and effectiveness without neglecting fundamental Islamic values. We recommend Islamic higher education to revitalize scientific traditions, build international collaborations, and adopt a multidisciplinary approach to effectively address modern challenges. This study makes an important contribution by emphasizing the need for a balance between innovation and Islamic values in producing graduates who are not only excellent in academic aspects but also have high social and moral awareness and are able to make real contributions to society.